PENGEMBANGAN DIRI DAN PEMBIASAAN DALAM PEMBELAJARAN “BAHASA” (Al Mah?ra: Jurnal Pendidikan Bahasa Arab, 2015)
AbctractThe Habituation in learning “language” is anessen tial and substan tialin terms of mastery and language skills including mastery and Arabiclanguage skills. Because the habituation is a basic requirement in thelearning “language” itself. For language learners tobe able to masterthelanguage being studied or taught in the learning needs of habituationand repetition continuously. On the other side of habituation languagewill have a positive influence on the development of language learnersthemselves. Therefore,the relation of the habituation in learning languageas an integral part of self-development for language learners. In this paperself-development approach used humanistic approach. This approach isseen to have compatibility with habituation in language learning